Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Since we have y = x + 3, we substitute this to the first equation so:

y - x = 4

x + 3 - x = 4

3 = 4

This is definitely not true, therefore there is no solution for the system.

y - x = 4

x + 3 - x = 4

3 = 4

This is definitely not true, therefore there is no solution for the system.